2021
DOI: 10.1038/s41598-021-93274-w
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of non-thermal effect of microwave radiation and its mode of action in bacterial cell inactivation

Abstract: A growing body of literature has recognized the non-thermal effect of pulsed microwave radiation (PMR) on bacterial systems. However, its mode of action in deactivating bacteria has not yet been extensively investigated. Nevertheless, it is highly important to advance the applications of PMR from simple to complex biological systems. In this study, we first optimized the conditions of the PMR device and we assessed the results by simulations, using ANSYS HFSS (High Frequency Structure Simulator) and a 3D parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 63 publications
0
36
0
Order By: Relevance
“…In vivo, necrosis may trigger an immune response or an inflammatory response [235], where physical factors in LTP are very relevant in direct treatment strategies. Furthermore, based on the results of a recent study, the effects of MW emission from a plasma were determined to have decontamination efficacy [236]. This transbarrier capacity of LTP treatment suggests the noninvasive potential in medical application but more extensive studies are needed to understand the mechanism of interaction of physically based modalities with cells and tissues.…”
Section: B Challenges and Proposed Solutionsmentioning
confidence: 99%
“…In vivo, necrosis may trigger an immune response or an inflammatory response [235], where physical factors in LTP are very relevant in direct treatment strategies. Furthermore, based on the results of a recent study, the effects of MW emission from a plasma were determined to have decontamination efficacy [236]. This transbarrier capacity of LTP treatment suggests the noninvasive potential in medical application but more extensive studies are needed to understand the mechanism of interaction of physically based modalities with cells and tissues.…”
Section: B Challenges and Proposed Solutionsmentioning
confidence: 99%
“…The application of MWs in cell inactivation also reflected the theory of the interaction of electric fields with specific molecules. Priyanka Shaw et al 47 found in a study of the inactivation of bacterial cells by MW irradiation that MWs can interact with molecules on the surfaces of bacterial cells, thereby causing changes in cell morphology and further leading to failure of the intracellular oxidative defence machinery and DNA damage-mediated inactivation of bacterial cells.…”
Section: Mechanisms Of the Nonthermal Effects Of Mwsmentioning
confidence: 99%
“…However, their ability to eliminate bacterial infections has not received enough attention. MW as a component of the electromagnetic spectrum, are non-ionizing radiation with frequencies ranging from 300 MHz to 300 GHz, and wavelengths between 1 m and 1 mm ( Mawioo et al, 2016 ; Wang et al, 2019a ; Shaw et al, 2021 ). The effects of MW include thermal and non-thermal ( Rougier et al, 2014 ; Shaw et al, 2021 ), and it is generally believed that the temperature increase caused by MW exposure plays a key role in microorganism inactivation ( Rougier et al, 2014 ; Shaw et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…MW as a component of the electromagnetic spectrum, are non-ionizing radiation with frequencies ranging from 300 MHz to 300 GHz, and wavelengths between 1 m and 1 mm ( Mawioo et al, 2016 ; Wang et al, 2019a ; Shaw et al, 2021 ). The effects of MW include thermal and non-thermal ( Rougier et al, 2014 ; Shaw et al, 2021 ), and it is generally believed that the temperature increase caused by MW exposure plays a key role in microorganism inactivation ( Rougier et al, 2014 ; Shaw et al, 2021 ). The MW-based thermal effect is different from conventional heating ( Shaw et al, 2021 ), involving the dielectric properties of polar substance molecules, which have a shorter heating time than conventional heating.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation